Mechanisms and therapeutic potential of chinonin in nervous system diseases - Hui, Zhang; Lai-Fa, Wang; Xue-Qin, Wang; Ling, Deng; Bin-Sheng, He; Li, Jian-Ming (Journal of asian natural products research, 2024)
The flavonoid compound chinonin is one of the main active components of Rhizoma anemarrhena with multiple activities, including anti-inflammatory and antioxidant properties, protection of mitochondrial function and regulation of immunity. In this paper, we reviewed recent research progress on the protective effect of chinonin on brain injury in neurological diseases. "Chinonin" OR "Mangiferin" AND "Nervous system diseases" OR "Neuroprotection" was used as the terms for search in PumMed. After discarding duplicated and irrelevant articles, a total of 23 articles relevant to chinonin published between 2012 and 2023 were identified in our study.